(untitled) (diségno, 2022)
The collective volume Mappe (Maps), the second in the Linguaggi Grafici (Graphic Languages) series, is proposed as a space for reflection on maps, considered among the most widely used graphic devices with transversal and different purposes, with the intention of exploring their various typologies, functions, uses, modes of expression and symbolic languages while investigating their potentialities, roles, areas of application and research perspectives. [read more]